Study on Isolation and Partial Purification of Lactase (β-galactosidase) Enzyme from Lactobacillus Bacteria Isolated from Yogurt (Journal of Scientific Research, 2011)
Lactase has many applications in dairy industry including for the treatment of lactose intolerance. The present study was conducted to identify the activity of lactase enzyme produced by Lactobacillus bacteria isolated from yogurts available in Dhaka city. The strains were identified to be gram positive, catalase negative, fermentative and lactase producer when cultured on selective MRS agar media by using standard bacteriological procedures and techniques. The study revealed that enzymes produced by lactobacilli were capable to produce glucose from substrate lactose in lactose modified media using lactase assay Kit Glu IB and their highest protein concentration (17.25 mg/ml) was observed in the supernatant of culture media isolated from L. lactis. Highest total activity (850.69 U/l) and specific activity (50.04 U/mg) of lactase enzyme was observed in the strain of L. bulgaricus. The crude extract which showed highest activity was further purified by ammonium sulphate precipitation followed by anion exchange column chromatography (DEAE cellulose). Final specific activity and fold purification of lactase enzyme reached to 62.80 U/mg and 1.47 respectively. The highest physic-chemical properties (Effect of pH and temperature) of lactase enzyme were observed at PH 6.0 which was 43.98 U/mg of protein and at 70°c temperature which was 111.11 U/mg of protein.Keywords: β-Galactosidase; Specific activity; DEAE cellulose; Fold purification; Yogurt.© 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v4i1.8478J. Sci. Res. 4 (1), 239-249 (2012)